The relationship between self-concept clarity, social cognition, self-esteem, and social comparison on mobile phone dependence among Chinese youth - Yumei, Huang; Ma’rof, Aini Azeqa; Abdullah, Haslinda; Mohd Khir, Azlina (Human Resource Management Academic Research Society, 2024)
This study examines the relationships between self-concept clarity, social cognition, self- esteem, and social comparison on mobile phone dependence among Chinese youth. Using a sample of 436 participants, this research employed quantitative methods, including Pearson correlation and multiple regression analyses, to explore these variables' predictive power. The results revealed that self-esteem was the strongest negative predictor of mobile phone dependence, followed by self-concept clarity, while social cognition and social comparison were positively correlated with higher dependence. These findings highlight the critical roles of self-perception and social cognitive processes in influencing mobile phone reliance. The study's implications suggest that fostering self-esteem, promoting self-concept clarity, and encouraging mindful digital practices could help mitigate mobile phone dependence among youth. These insights offer valuable guidance for educators, policymakers, and institutions aiming to address the growing issue of mobile phone overuse in Chinese society